Implementation of Differentiated Learning by Leading Teachers - Andini Nurul Khotimah; Machdalena Vianty; Eryansyah (Universitas Pendidikan Ganesha, 2025)
The implementation of differentiated learning by driving teachers is one of the strategic efforts in realizing education that is student-centered in accordance with policy Merdeka Belajar. Each student has differences in terms of abilities, interests, learning styles, and learning needs. Differentiated learning is a learning approach that can accommodate students' learning needs. In differentiated learning, there are four aspects such as content, process, product, and learning environment. This study aims to determine the application of differentiated learning, challenges in implementing differentiated learning, and strategies to overcome challenges in implementing differentiated learning by English Teachers of Public High Schools. The selected sample was two English Teachers of Public High Schools in Palembang. In this study, semi-structured interviews were used to collect data. This research is a qualitative study. Furthermore, thematic analysis was used to analyze the data. Based on the results of the study, it shows that English Teachers of Public High Schools in Palembang use cognitive and non-cognitive diagnostic assessments to determine students' readiness, interests, and learning styles before implementing differentiated learning after which they use differentiated learning content, process, and product in the teaching and learning process. The implications of this study can contribute to improving the quality of learning by emphasizing that differentiation is not just an additional strategy, but a primary approach in creating inclusive and student-centered learning.